Theoretical Insight Into Diamond Doping and Its Possible Effect on Diamond Tool Wear During Cutting of Steel - Hao, Li; Manzhos, Sergei; Zhang, Zhijun (Frontiers in Materials, 2021)
Natural diamond tools experience wear during cutting of steel. As reported in our previous work, Ga doping of diamond has an effect on suppressing graphitization of diamond which is a major route of wear. We investigate interstitial and substitutional dopants of different valence and different ionic radii (Ga, B, and He) to achieve a deeper understanding of inhibiting graphitization. In this study, ab initio calculations are used to explore the effects of three dopants that might affect the diamond wear. We consider mechanical effects via possible solution strengthening and electronic effects via dopant-induced modifications of the electronic structure. We find that the bulk modulus difference between pristine and doped diamond is clearly related to strain energies. Furthermore, boron doping makes the resulting graphite with stable sp2 hybridization more perfect than diamond, but Ga-doped diamond needs 2.49 eV to form the two graphene-like layers than only one layer, which would result in the suppressed graphitization and reduced chemical wear of the diamond tool.